Memsahib's chronicles - "Malik, Suchita" (New Delhi, 2011)
This is the story of Raghu and Sunaina, who in their two decades in the civil service, are accustomed to a world of power and glamour. This book provides a glimpse, through the dispassionate eyes of Sunaina, into the immensely private world of civil servants and especially the 'memsahibs' who are its unacknowledged backbone.
Keywords: Fiction